The Effect of Product Quality and Service Quality on Consumer Loyalty at Café Ente with Consumer Satisfaction as an Intervening Variable - Milawati Milawati; Fenni Supriadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to identify the effect of product quality and service quality on consumer loyalty at Café Ente, mediated by consumer satisfaction. The study uses a quantitative approach with an associative design. The sampling technique used is purposive sampling. The population in this study is all consumers who have visited and purchased products at Café Ente. The number of respondents is 100 consumers who met the requirements of purposive sampling. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of SmartPLS 3 software. The results show that direct testing indicates that the variables of product quality and service quality affect consumer satisfaction, and consumer satisfaction directly affects loyalty. Meanwhile, other direct testing results indicate that the variables of product quality and service quality do not affect consumer loyalty. Furthermore, based on the indirect testing results, it is known that both product quality and service quality have an indirect effect on consumer loyalty through the mediating role of consumer satisfaction. Future research is recommended to include other variables that may influence consumer loyalty, such as price, brand image, customer experience quality, and promotion, as well as to expand the research object to different types of businesses or regions so that the results obtained can provide a more comprehensive understanding.